Produção e qualidade de inhame (Dioscorea sp) em função de doses de nitrogênio e potássio - Silva, Ovídio Paulo Rodrigues da (2017)
The yam responds to nitrogen and potassium fertilization with increased production and improvement in the quality of tubers. In view of the above, the purpose of this work was to evaluate the yield and quality of the yam as a function of nitrogen and potassium doses. The experiment was carried out under field conditions at the Agricultural Sciences Center of the Federal University of Paraíba, Areia-PB, Brazil, and used the experimental design in randomized blocks, with treatments distributed in a 5 x 5 factorial arrangement, corresponding to five nitrogen doses ( 0, 60, 120, 180, 240 kg ha-¹), and five doses of potassium (0, 60, 120, 180, 240 kg ha-¹) with four replicates. The experimental plots consisted of 60 plants (six rows of 10 plants), spaced 1.2 x 0.6 m, and the useful area was composed of 32 plants contained in the central rows. The evaluated characteristics were the average mass of commercial tubers, total and commercial yields of tubers, percentage of nematode infected tubers, starch, gray and moisture contents, SPAD index and leaf contents of N, P and K. The results were submitted to the analysis of variance, using the F test and polynomial regression analysis to evaluate the effect of nitrogen and potassium doses on the evaluated characteristics. The average mass, total and commercial productivity were influenced in isolation by the nitrogen and potassium doses, and the commercial productivity surpassed the national average. The percentage of tubers with symptoms of nematode attack reduced with nitrogen and potassium doses. The interaction between nitrogen and potassium provided a reduction in the starch content and increased the ash content in the yams' tubers, and the moisture content increased with the nitrogen and potassium doses. Foliar N and K contents increased as a function of nitrogen and potassium rates, and the P content decreased.